Analysis of Indonesia-Netherlands Diplomatic and Consular Relations - priambodo, gabriella dewa (Journal of ASEAN Dynamics and Beyond, 2021)
In order to improve the quality of international cooperation, the Indonesian nation must be able to improve the quality and performance of foreign officials so that they are able to carry out proactive diplomacy in all fields to build a positive image of Indonesia in the international world. Through this article, the diplomatic relations between Indonesia and the Netherlands will be analyzed specifically, both diplomatic and consular relations. The result,diplomatic relations between the governments of Indonesia and the Netherlands have been in accordance with Law Number 37 of 1999, but in practice it has not been implemented properly in accordance with the applicable laws and regulations, so on this occasion I will discuss further about diplomatic relations between Indonesia and the Netherlands which had temporarily interrupted by several influencing factors including the revocation of the Dutch embassy in Indonesia named Rob Swartbol due to protests against the execution by the Indonesian government against a Dutch citizen named Ang Kim Soe or vice versa the revocation of the Indonesian embassy in the Netherlands because it will be held consultations by their respective countries, both the Netherlands and Indonesia, on their embassies.